The Impact of Mobile Marketing, Personalization, and Customer Engagement on Purchase Decisions - Rah Utami Nugrahani; Yudiyanto Joko Purnomo; Mahmuddin; Marjuki (Journal Management & Economics Review (JUMPER), 2026)
With the advancement in digital technology, marketing strategies and consumer behavior are becoming more and more influenced by mobile technologies. The objective of this paper is to evaluate the impact of mobile marketing, personalization, and customer engagement on the purchase decision of the consumer. In order to collect the required data, quantitative research methodology was employed using survey methodology, where data were collected from the individuals who have undergone marketing processes through mobile and also engaged in online purchases. Data analysis was done using multiple linear regression. From the results, it is evident that mobile marketing, personalization, and customer engagement all influence purchase decision positively. Out of the above-mentioned variables, customer engagement emerges as the most dominating variable affecting the purchase behavior of the consumer. From coefficient of determination, it is found that the above-mentioned independent variables significantly explain a considerable amount of variance in purchase decisions, the remaining variances being explained by some other variables not included in the model.